2017
DOI: 10.1021/acs.chemmater.7b03096
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Time-Resolved Attenuated Total Reflectance Infrared Spectroscopy for Probing Metal–Organic Framework Thin Film Growth

Abstract: In situ chemical measurements of solution/surface reactions during metal-organic framework (MOF) thin film growth can provide valuable information about the mechanistic and kinetic aspects of key reaction steps, and allow control over crystal quality and material properties. Here, we report a new approach to study the growth of MOF thin films in a flow cell using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). Real-time spectra recorded during continuous flow synthesis were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…This is a key step to rapidly form H-MOF crystals. 41,42,65 Meanwhile, the introduced DMOA surfactant forms supramolecular micelles through self-assembly, a key step to generate mesopores and macropores. 64 Upon the addition of (Cu, Zn) HDS to the micelle solution, the Cu 2+ and BTC 3À rapidly selfassemble on the surface of the template micelles due to the high anion exchange rate.…”
Section: Resultsmentioning
confidence: 99%
“…This is a key step to rapidly form H-MOF crystals. 41,42,65 Meanwhile, the introduced DMOA surfactant forms supramolecular micelles through self-assembly, a key step to generate mesopores and macropores. 64 Upon the addition of (Cu, Zn) HDS to the micelle solution, the Cu 2+ and BTC 3À rapidly selfassemble on the surface of the template micelles due to the high anion exchange rate.…”
Section: Resultsmentioning
confidence: 99%
“…19,11 Tejedor-Tejedor et al 20 showed that ATR is suitable for monitoring the hydrolysis of TEOS, and it has also been used to study the formation of mesoporous films in dip coating. [21][22][23] To our knowledge, the presented study is the first to follow the formation of mesoporous particles using in situ ATR.…”
Section: Introductionmentioning
confidence: 93%
“…The obtained HKUST-1 film shows a well-behaved crystallization according to the XRD results (Panel (ii) of Figure a), in which the HKUST-1’s patterns are in accordance with the simulated patterns. The MOF coating showed a stable adhesion because of the partially unconverted ZnO layer. , …”
Section: Mof Filmsmentioning
confidence: 99%
“…(iii) Time-resolved infrared absorption spectra for surface reactions to form the HKUST-1 film. Adapted with permission from ref . Copyright American Chemical Society 2017.…”
Section: Mof Filmsmentioning
confidence: 99%
See 1 more Smart Citation